Implementasi Pengukuhan Akhlak Melalui Pendidikan Anti Korupsi Dalam Kajian Agama Islam - Nym Dinda Harni Bina Imania (Ganesha Civic Education Journal, 2022)
Corruption as a moral crime is a bad behavior that knows no boundaries of age, profession, religious background, social background, economic background and even a person’s level of education. Acts of corruption that continue to occur and become entrenched among the people make human morals and ethics increasingly dilapidated. Corruption has its essence as an abuse of power or authority that aims solely to benefit oneself and harm others. Prevention of corruption is a common task that needs to be addressed immediately, by providing anti corruption education through strengthening morals and character which is implemented in religious-based moral education. The purpose of this study among others to show some information about the weightiness of anti-corruption education in order to fortify oneself from corrupt behavior. And the application of the research method is this manuscript is to use a qualitive method by blunting the study of the literature.